microRNA-195 attenuates neuronal apoptosis in rats with ischemic stroke through inhibiting KLF5-mediated activation of the JNK signaling pathway - Lisha Chang; Wan Zhang; Songxin Shi; Yanbo Peng; Dali Wang; Li Zhang; Jiang Zhang (BMC, 2020)
Abstract Background Accumulating evidence has implicated the regulation of microRNAs (miRs) in ischemia stroke. The current study aimed to elucidate the role of microRNA-195 (miR-195) in neuronal apoptosis and brain plasticity in rats with ischemic stroke via the JNK signaling pathway/KLF5 axis. Methods Ischemic stroke rat models were established by middle cerebral artery occlusion (MCAO), and oxygen deprivation (OGD) models were constructed in rat neuronal cells, followed by gain- or loss-of-function of miR-195 and/or KLF5 in rats and cells. Infarct volume, neuronal loss and ultrastructure, the expression of GAP-43, SYP and KLF5 protein as well as cell apoptosis were determined in the rats. Caspase-3 activity as well as the expression of miR-195, KLF5, GAP-43, SYP, JNK, phosphorylated JNK, Bax and Bcl-2 was measured in the cells. Results The infarct size, expression of GAP-43 and SYP protein and apoptotic cells were increased in the miR-195−/− MCAO rats, while reductions were detected in the miR-195 mimic MCAO and KLF5−/− MCAO rats. Bcl-2 expression was increased, Bax and Caspase-3 expression as well as the ratio of phosphorylated JNK/JNK was decreased in response to miR-195 overexpression or KLF5 knockdown. Interestingly, the silencing of KLF5 reversed the effects exerted by the miR-195 inhibitor on the expression of Bcl-2, phosphorylated JNK/JNK, Bax and Caspase-3. Conclusions Collectively, our study unraveled that miR-195 could down-regulate KLF5 and block the JNK signaling pathway, ultimately inhibiting neuronal apoptosis in rats with ischemic stroke.